2021
DOI: 10.14202/vetworld.2021.2273-2281
|View full text |Cite
|
Sign up to set email alerts
|

Feeding value of sorghum stover fed to tropical hair sheep as complete rations in chop, mash, pellet, and block forms

Abstract: Background and Aim: Poor palatability, low bulk density, and low nutritive value restrict the utilization of the crop residues as animal feeds. Altering the physical characteristics of feed by blending the roughage and concentrates in the form of complete feed improves the nutrient use efficiency and reduces the feed wastage, feed cost, and labor cost. The study aims to determine suitable processing methods (mash, pellet, or block forms) for efficient utilization of sorghum stover-based complete rations vis-a-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
3
3
0
Order By: Relevance
“…The percentage of dry matter intake relative to body weight did not differ substantially between the loose and pelleted diets (3.3% and 3.01%), our results did not agree with [19], what he found to be the percentage of dry matter intake relative to body weight significant differences between the loose and pelleted diets. The pelleted diet produced 1 kilogram of weight gain at a significantly lower cost (4,238 Iraqi dinars) than the loose diet (5,557 Iraqi dinars), this result agrees with [21] while [19], no significant difference was observed in the cost of producing 1 kg of weight gain between the loose and pelleted diets. The interaction between the rearing system and the physical form of the complete mixed ration revealed that the individual rearingpelleted form consumed significantly more feed per day (1,302 g/day) than the group rearing -pelleted form (1078 g/day) and the group rearing -loose form (1,108 g/day), but did not differ significantly from the overlap of the individual rearing -loose form (1,156 g/day).There were no significant differences in dry matter consumption across all interventions.…”
Section: Feeding Performancesupporting
confidence: 77%
See 2 more Smart Citations
“…The percentage of dry matter intake relative to body weight did not differ substantially between the loose and pelleted diets (3.3% and 3.01%), our results did not agree with [19], what he found to be the percentage of dry matter intake relative to body weight significant differences between the loose and pelleted diets. The pelleted diet produced 1 kilogram of weight gain at a significantly lower cost (4,238 Iraqi dinars) than the loose diet (5,557 Iraqi dinars), this result agrees with [21] while [19], no significant difference was observed in the cost of producing 1 kg of weight gain between the loose and pelleted diets. The interaction between the rearing system and the physical form of the complete mixed ration revealed that the individual rearingpelleted form consumed significantly more feed per day (1,302 g/day) than the group rearing -pelleted form (1078 g/day) and the group rearing -loose form (1,108 g/day), but did not differ significantly from the overlap of the individual rearing -loose form (1,156 g/day).There were no significant differences in dry matter consumption across all interventions.…”
Section: Feeding Performancesupporting
confidence: 77%
“…The process of compressing feed into pellet reduces the feed's volume and increases its density, resulting in a decrease in the rumen full and a subsequent increase in the amount of voluntary feed intake [20,22]. In terms of the feed conversion ratio, the pelleted diet was superior to the loose diet (4.56, 5.99 respectively ), confirming the findings of [16] and [21], whereas [18,20], did not observe a significant difference between the pelleted diet and the loose diet, and it was mentioned [20], that pelletizing the feed does not always improve the feed conversion ratio. The pelleted diet was superior to the loose diet in terms of feeding efficiency (223, 172 gm weight gain / kg dry matter ), which may be attributable to the increased digestibility of nutrients as a result of pelleting the feed and the absence of energy losses during digestion [16].…”
Section: Feeding Performancesupporting
confidence: 71%
See 1 more Smart Citation
“…Pi et al (2005) found that feeding pelletized rice straw-based total mixed diet resulted in higher intake, daily weight growth, and feed efficiency in Boer goats than ryegrass hay-based rations. In addition, Raju et al (2021) reported that the higher weight gain and average daily gain in pelleted diets are reflected by increased digestibility of OM, CP and NDF.…”
Section: Growth Performancementioning
confidence: 99%
“…However, straw is a low-quality dry fodder that is fed as filler to cattle since it has little nutritional value. Minerals, vitamins and proteins are all in short supply (Raju et al, 2021). Even the carbohydrate is also of low quality having just 40%-50% digestibility.…”
Section: Overcoming the Dry Fodder Shortagementioning
confidence: 99%